Function Analysis Of South Sulawesi Traditional Media In Conveying Messages To The Public - Muslimin M, Andi Ernie Zaenab Musa, Anwar Soleh Purba, Muhammad Tang (International Journal of Advanced Science and Technology, 2020)
Traditional media has taken part in conveying messages to the public, especially in the public whose scope is in rural society. Traditional media has become local wisdom that has a unique value in conveying messages. The purpose of this study was to explore the function of South Sulawesi traditional media in conveying messages to the public. Data collection used a qualitative descriptive method and the data was natural which means the field data was adjusted to natural conditions that occur in the field without being engineered. The results of the study showed that traditional media has several functions namely, entertainment and creativity media function, education and da'wah function, promotion and information provision function, socialization and political propaganda function, critics and social control function, and cultural preservation function. This study concluded that traditional media is very effective in conveying messages to the public.